Knowledge and Perception of Indigenous-Inspired Spa among Entrepreneurial Undergraduate Students at Faculty of Hospitality, Tourism and Wellness, Universiti Malaysia Kelantan - Marican, Nor Dalila; Nazir, Mohd Hakam; Hasbollah, Hasif Rafidee (Semarak International Journal of Future Tourism and Hospitality Management, 2025)
In Malaysia, the development of Indigenous-inspired spas provides not only economic opportunities but also supports cultural sustainability. The purpose of this study was to assess the knowledge and perceptions of Indigenous-inspired spas among entrepreneurial undergraduate students. A cross-sectional survey was conducted involving 358 students enrolled in entrepreneurial related programs at the Faculty of Hospitality, Tourism, and Wellness, Universiti Malaysia Kelantan. The results demonstrated that while participants held generally favorable perceptions, their overall knowledge was limited. Product knowledge (r = 0.652, p < 0.001) and service knowledge (r = 0.660, p < 0.001) showed moderate positive correlations with perception, while operation knowledge demonstrated a moderate negative correlation (r = -0.511, p < 0.001). Educational interventions and specialized training modules should be developed to enhance students’ competencies, address misconceptions, and prepare future wellness, tourism, and hospitality entrepreneurs for active involvement in Malaysia’s Indigenous-inspired spa industry.